2022
DOI: 10.1039/d2cc02124b
|View full text |Cite|
|
Sign up to set email alerts
|

Rational design of a meso phosphate-substituted pyronin as a type I photosensitizer for photodynamic therapy

Abstract: Type I photodynamic therapy (PDT) with less oxygen consumption shows great potential to overcome malignant hypoxia in solid tumors. Herein, a novel meso phosphate substituted pyronin PY-P and its nanoparticles...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Compared to other PSs, the SN series has an ultralow concentration of phototoxicity. 12,18,19,[43][44][45][46][47] (Table S5, ESI †) This finding indicates the great potential of the SN series for PDT treatment. To investigate the subcellular targeting ability of the SN complex, the SN series was coincubated with 4T-1 cells.…”
Section: Cell Imaging and Pdt In Vitromentioning
confidence: 80%
“…Compared to other PSs, the SN series has an ultralow concentration of phototoxicity. 12,18,19,[43][44][45][46][47] (Table S5, ESI †) This finding indicates the great potential of the SN series for PDT treatment. To investigate the subcellular targeting ability of the SN complex, the SN series was coincubated with 4T-1 cells.…”
Section: Cell Imaging and Pdt In Vitromentioning
confidence: 80%
“…27 Introduction of electron-deficient acceptor units to photosensitizers may offer an effective way for the construction of type I photosensitizers, which can not only improve the electron affinity but also stabilize the external electrons, thus facilitating the formation of PS •− . 28 PDT-induced oxidation of biomolecules (e.g., NADH, GSH, lipid, etc.) is considered one of the main factors for killing cancer cells.…”
Section: •−mentioning
confidence: 99%
“…71 Wang's group reported a Fig. 10 Chemical structures of 14-15 64,65 and 16-19. [67][68][69][70] glutathione-hydrogen peroxide (GSH-H 2 O 2 ) co-responsive aPS with a dual type photosensitizing capability.…”
Section: Cationic Type I Pssmentioning
confidence: 99%
“…Zhou et al reported pyronin-based type I PS ( 15 ) with strong electron-withdrawing phosphate group. 65 The optimized LUMO level of −5.66 eV and presumable existence of five representative resonance structures endowed 15 with the potential to generate and stabilize the radical anions through a type I process. However, 15 was susceptible to nucleophilic reagents due to the high electrophilicity at the meso position.…”
Section: Pdt Monotherapymentioning
confidence: 99%